(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The aim of this paper is to reflect on the subject of ethnic authorities in the jurisdiction of Tucuman between the late eighteenth and early nineteenth centuries. We hypothesize that the maintenance of community structures and collective ownership of lands was the result, among other things, of the ability to redraw the characteristics of ethnic authorities and reconfigure their power. From the case of Colalao and Tolombón, we will try to show that in the finisecular period the system of ethnic authorities became more flexible and open (though not totally random), redefining not only the forms of access or profiles of caciques and alcaldes but also deepening their mutual overlap, blurring the boundaries between each other and gradually exchanging their roles and functions. In this context of transformation, the caciques will not base their legitimacy on rigid hereditary principles but neither the alcaldes will settle their legitimacy solely on elective principles because, although with greater flexibility, yet in the late eighteenth century the networks woven by different actors will work as one of the access roads to the system of ethnic authorities